Role of interventions in diagnosis and management of lung disorders in rheumatic diseases - Venkata Nagarjuna Maturu; Chetan Rao Vaddepally; V Pratibh Prasad (Indian Journal of Rheumatology)
Pulmonary manifestations of rheumatic diseases are common and lead to significant morbidity. Rheumatic diseases can affect the lung parenchyma, the interstitium, airways, pleura as well as the mediastinum. The pulmonary manifestation can be a part of the active disease, or be because of infectious complications, drug-induced changes, or pulmonary manifestations of other organ failure. It is hence important to diagnose early and appropriately, and treat aggressively. Interventional Pulmonology, a subspecialty of pulmonary medicine helps in diagnosis of these pulmonary manifestations. Interventional pulmonology procedures also help to treat central airway obstruction. Various modalities like bronchoscopy, endobronchial ultrasonography and thoracoscopy are now available. This article focuses on these modalities, the procedures which can be performed (bronchoalveolar lavage, endobronchial biopsy, forceps and cryo transbronchial lung biopsies, transbronchial needle aspiration) and the indications for the same.